Robotic Transthoracic Primary Repair of a Diaphragmatic Hernia and Reduction of an Intrathoracic Liver. Issue 1 (January 2018) - Counts, Sarah J.; Saffarzadeh, Areo G.; Blasberg, Justin D.; Kim, Anthony W.
This case involves a 70-year-old woman who presented after a low-speed motor vehicle collision with a traumatic right hemidiaphragm rupture and herniation of the liver into the right chest. She was brought to the operating room for a robotic-assisted minimally invasive transthoracic repair of this hernia with diaphragm plication. The case and video described in this report highlight the utility of the robotic platform in performing a transthoracic diaphragm repair and plication after a right-sided traumatic diaphragm rupture in a patient without concomitant abdominal injuries.